Groundwater Characteristics and Assessment (International Journal of Food and Nutritional Sciences, 2022)
The groundwater system is very important to both mankind and the environment. Aquifers are classified as confined, unconfined, leaky aquifers, or fractured aquifers according on the existence or lack of water table placement. The goal of this chapter is to explore groundwater characteristics and evaluation in the context of vertical Ground water (GW) distribution at all regional and municipal sizes, hydrological systems kinds, SW-GW interaction kinds, and SW-GW interaction The materials' physical qualities determine the aquifer's properties, which are determined using Surveys of resistivity and pumping experiments are accompanied by distant sense and geographical data systems for better groundwater system information. In watershed management, such as risk administration and aquifer systems assessment, it is also vital to investigate the SW-GW interactions utilizing readily available approaches.